2021
DOI: 10.3389/fimmu.2021.601080
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent COVID-19 Patients Without Comorbidities Display Similar Immunophenotypes Over Time Despite Divergent Disease Severities

Abstract: COVID-19, the disease caused by SARS-CoV-2 infection, can assume a highly variable disease course, ranging from asymptomatic infection, which constitutes the majority of cases, to severe respiratory failure. This implies a diverse host immune response to SARS-CoV-2. However, the immunological underpinnings underlying these divergent disease courses remain elusive. We therefore set out to longitudinally characterize immune signatures of convalescent COVID-19 patients stratified according to their disease severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
(113 reference statements)
1
3
0
Order By: Relevance
“…2c). These findings are consistent with prior studies demonstrating a decrease in circulating monocytes during convalescent COVID-19 infection 25, 26 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2c). These findings are consistent with prior studies demonstrating a decrease in circulating monocytes during convalescent COVID-19 infection 25, 26 .…”
Section: Resultssupporting
confidence: 93%
“…In addition, these studies showed that monocytes in convalescent individuals display increased levels of inflammatory genes [21][22][23][24] , antigen presentation molecules, including HLA-DQA and HLA-DPA 20 , and the activation marker CD169 21 . However, other studies have demonstrated a decrease in monocyte percentages in convalescent individuals including those who had severe disease 25,26 . While a growing body of research has shed light on monocyte behavior during the convalescent phase, contrasting findings underscore the need for more detailed studies to unravel these complexities.…”
Section: Introductionmentioning
confidence: 94%
“…In this module, we also identified several hub-high traffic genes that were crucial in regulating the host immune response during COVID-19. These hub-high traffic genes included CDKN2A (308,309), OASL (282,310), CCL5 (311)(312)(313)(314)(315)(316), KIF2C (4), and CD8A (317). Among them, the CCL5 hub-high traffic gene has the most important role in regulating the inflammatory response and the host immune system; however, its excessive expression can amplify inflammatory responses toward immunopathology (e.g., cytokine storm) (311,314).…”
Section: Midnightblue Modulementioning
confidence: 99%
“…The convalescent period after infection is susceptible to different complications, especially with distinct immunological signatures that open an "immunological window," allowing the development of complications such as acute myocardial infarction and myocarditis, among other clinical manifestations 27 , 28 . Therefore, the morphophysiological parameters were collected after recovery from the acute sequelae recorded within the subdivision of symptoms (mild, moderate, and severe/critical).…”
Section: Discussionmentioning
confidence: 99%